Bone regeneration material consisting of biodegradable fibers containing tricalcium phosphate particles
By incorporating amorphously modified tricalcium phosphate particles into biodegradable fibers with β-TCP particles, the bone regeneration material achieves early and sustained ion release, addressing the limitations of crystalline β-TCP particles in promoting effective bone formation.
Patent Information
- Application Number
- JP2024571918
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-09-20
- Filing Date
- 2024-09-06
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2044-09-06
AI Technical Summary
Existing bone regeneration materials using crystalline β-TCP particles struggle to continuously release calcium ions/phosphate ions and other beneficial ions effectively for prolonged bone formation, especially during the early stages of bone implantation.
The development of biodegradable fibers containing a combination of β-TCP particles and amorphously modified tricalcium phosphate particles (m-CP particles), where the m-CP particles are produced by bead milling to enhance early dissolution and continuous release of ions, while preventing aggregation through the use of an anhydrous solvent in the spinning solution.
This approach enables early and sustained release of calcium ions/phosphate ions and other ions, promoting effective bone formation and reducing the risk of aggregation, which can impede early bone regeneration.
Smart Images

Figure 0007657438000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a bone regeneration material comprising a biodegradable fiber containing tricalcium phosphate particles. [Background technology]
[0002] β-phase tricalcium phosphate (β-TCP) is widely used as an osteogenic factor in bone regeneration materials. Existing bone regeneration materials using β-TCP particles include a granular type (OSFERION, registered trademark) and a type in which β-TCP particles are incorporated into biodegradable fibers (REBOSSIS, registered trademark). In the latter, the β-TCP particles contained in the biodegradable resin dissolve when they come into contact with body fluids as the biodegradable resin decomposes, releasing calcium ions and phosphate ions to promote bone formation.
[0003] When the bone regenerative material is implanted in the affected area, the β-TCP particles dissolve on contact with body fluids, releasing calcium ions and phosphate ions. In order to initiate early bone formation, it is desirable for the release of calcium ions and phosphate ions from the β-TCP particles to begin as soon as possible after the bone regenerative material is implanted in the affected area. However, because bone formation takes time, it is desirable for the necessary amounts of calcium ions and phosphate ions to be gradually and continuously supplied in accordance with the progress of bone formation in the affected area after the bone regenerative material is implanted in the affected area.
[0004] Furthermore, it has been reported that bone formation in the affected area can be further promoted by supplying other biofunctional ions (silicon, boron, magnesium, etc.) in addition to calcium ions / phosphate ions. [Prior art documents] [Patent documents]
[0005] Patent Document 1: Patent No. 6251462 [Non-patent literature]
[0006] Non-Patent Document 1: Creation of metal ion release scaffold material based on the activation mechanism of osteoblasts Materia Vol. 59 No. 11 (2020) Akiko Obata, Toshihiro Kasuga Summary of the Invention [Problem to be solved by the invention]
[0007] Under these circumstances, there was a need for a bone regenerative material that would, after implantation in the affected area, begin to release calcium ions, phosphate ions, and other ions effective in bone formation early on, and would continue to release these ions gradually while bone formation progresses, thereby realizing effective bone formation.However, it was difficult to achieve all of these functions using crystalline β-TCP particles. [Means for solving the problem]
[0008] As a result of extensive research aimed at solving the above problems, the inventors of the present invention came up with the idea of preparing particles (m-CP particles) in which the crystal structure of β-TCP is modified to an amorphous state by applying impact to β-TCP particles using a bead mill, and then incorporating the m-CP particles together with β-TCP particles in biodegradable fibers. β-TCP particles and m-CP particles have different dissolution rates, so by incorporating both, it is possible to quickly elute calcium ions / phosphate ions from the m-CP particles, and then to continuously and gradually release calcium ions / phosphate ions from the β-TCP particles. In addition, when the m-CP particles are subjected to impact, the crystal bonds are broken and the particles are ionized to release phosphate ions (PO4) 3- is negatively charged, it is possible to coordinate positively charged metal or metalloid ions. However, when the particle size is made very small by bead milling, it is easy for the particles to aggregate in the fiber. If the particles aggregate, it takes a long time for the particles to come into contact with body fluids after implantation in the body, making early bone formation difficult. The inventors of the present invention have discovered that by using an anhydrous solvent in the preparation of the spinning solution, the particles can be prevented from agglomerating with each other in the fiber and can be uniformly dispersed.
[0009] Based on the above-mentioned ideas and discoveries, the inventors of the present invention have proposed a bone regeneration material comprising a biodegradable fiber containing tricalcium phosphate particles, The bone regeneration material is formed of biodegradable fibers having an outer diameter of 60 to 200 μm that are entangled with each other to form a cotton-like shape, The biodegradable fiber contains 35 to 85% by weight of tricalcium phosphate particles and 15 to 65% by weight of polylactic acid-glycolic acid copolymer (PLGA resin) as the remainder, The tricalcium phosphate contains β-phase tricalcium phosphate particles (β-TCP particles) having a diameter of 0.5 to 5 μm and tricalcium phosphate particles (m-CP particles) obtained by crushing the β-TCP particles to a diameter of 0.1 to 0.5 μm by bead milling and modifying them into an amorphous phase, in a weight ratio of 5 to 50:95 to 50, The biodegradable fiber is spun from a spinning solution prepared using an anhydrous solvent, and the m-CP particles are dispersed around the β-TCP particles in the fiber without agglomeration. The inventors have arrived at the invention of a bone regeneration material comprising biodegradable fibers containing the above-mentioned tricalcium phosphate particles.
[0010] Preferably, the biodegradable fiber contains 50-75% by weight of tricalcium phosphate particles and 50-25% by weight of PLGA resin, and the tricalcium phosphate particles contain the β-TCP particles and the m-CP particles in a weight ratio of 10-25:90-75.
[0011] Preferably, the PLGA resin is a D-form containing PDLLGA resin and the anhydrous solvent is acetone.
[0012] Preferably, the m-CP particles are prepared by wet-milling β-TCP particles with acetone.
[0013] Preferably, the m-CP particles contain metal ions (eg, magnesium ions, silver ions) or metalloid ions (eg, boron ions, silicon ions).
[0014] Preferably, the m-CP particles contain silver ions, and a bone regeneration material containing the m-CP particles containing silver ions exhibits antibacterial properties.
[0015] Preferably, the biodegradable fibers of the bone regeneration material of the present invention are spun using a wet spinning method.
[0016] The outer diameter of the biodegradable fibers in the bone regeneration material of the present invention is preferably 80 to 160 μm, more preferably 100 to 120 μm.
[0017] The inventors of the present invention further disclose a method for producing a bone regenerating material comprising biodegradable fibers containing tricalcium phosphate particles, comprising the steps of: β-phase tricalcium phosphate particles (β-TCP particles) were milled to a diameter of 0.1 to 0.5 μm using a bead mill to prepare amorphous phase modified tricalcium phosphate particles (m-CP particles). A spinning solution is prepared by mixing 30 to 80% by weight of β-TCP particles having a diameter of 0.5 to 5 μm, 5 to 35% by weight of the m-CP particles, and 15 to 65% by weight of PLGA resin in acetone with stirring; The spinning solution is spun into a biodegradable fiber by a wet spinning method, the biodegradable fiber has an outer diameter of 60 to 200 μm, and the m-CP particles are dispersed surrounding the β-TCP particles in the fiber without agglomeration, The spun biodegradable fibers are washed with ethanol and dried at room temperature to recover a bone regeneration material in which the biodegradable fibers are entangled with each other to form a cotton-like shape. The inventors have arrived at an invention relating to a method for producing a bone regenerating material comprising biodegradable fibers containing the above-mentioned tricalcium phosphate particles.
[0018] Preferably, the biodegradable fiber contains 40 to 70% by weight of the β-TCP particles, 5 to 15% by weight of the m-CP particles, and 15 to 65% by weight of the PLGA resin.
[0019] Preferably, the PLGA resin is a D-form containing PDLLGA resin and the anhydrous solvent is acetone.
[0020] Preferably, the m-CP particles are prepared by wet-milling β-TCP particles with acetone.
[0021] Preferably, the method includes the step of incorporating metal or metalloid ions into the m-CP particles. Effect of the Invention
[0022] In the bone regeneration material produced by the method of one embodiment of the present invention, the small-sized m-CP particles are dispersed within the fibers surrounding the β-TCP particles without agglomerating. Therefore, after the bone regeneration material is implanted into the affected area, the m-CP particles dissolve upon contact with body fluids, quickly releasing calcium ions / phosphate ions, and then the β-TCP particles dissolve later, continuously and gradually releasing calcium ions / phosphate ions, thereby achieving effective bone formation.
[0023] The bone regeneration material produced by the method of one embodiment of the present invention uses PDLLGA resin, which has a fast decomposition rate, as a biodegradable fiber. Therefore, after the bone regeneration material is implanted into the affected area, the PDLLGA resin quickly decomposes when it comes into contact with body fluids, and calcium ions / phosphate ions are quickly eluted.
[0024] The biodegradable fibers constituting the bone regeneration material produced by the method of one embodiment of the present invention are spun using a spinning solution prepared by dissolving PDLLGA resin in anhydrous acetone, so that the tricalcium phosphate particles do not bond to each other and no particle aggregation occurs within the fibers.
[0025] The m-CP particles contained in the biodegradable fibers of the bone regeneration material of the present invention have a small particle size of 0.1 to 0.5 μm, a large specific surface area, and are amorphous and negatively charged, making it possible to coordinate metal ions or metalloid ions such as magnesium ions, boron ions, silver ions, silicon ions, etc. When a bone regeneration material carrying these metal ions or metalloid ions on its fibers is implanted in a living body, the biodegradable fibers are dissolved in contact with body fluids, and these metal ions and metalloid ions can be eluted from the m-CP particles contained in the fibers together with calcium ions / phosphate ions.
[0026] The biodegradable fibers that make up the bone regeneration material produced by the method of one embodiment of the present invention are spun using a spinning solution prepared by dissolving PDLLGA resin in anhydrous acetone, and are therefore safer than those using chlorine-based solvents such as chloroform.
[0027] The biodegradable fibers constituting the bone regenerating material produced by the method of one embodiment of the present invention are spun using a wet spinning method, and therefore the production costs are lower than when electrospinning is used. [Brief description of the drawings]
[0028] [Figure 1] FIG. 1 shows a cotton-shaped bone regeneration material made of biodegradable fibers of the present invention. [Diagram 2] FIG. 2 shows a schematic diagram of the composition of the biodegradable fiber of the present invention containing β-TCP particles and m-CP particles. [Diagram 3] FIG. 3 shows a cross section of a biodegradable fiber containing β-TCP particles and m-CP particles of the present invention. [Figure 4] FIG. 4 shows a scanning electron microscope photograph (SEM photograph) of a cross-section of a biodegradable fiber of the present invention cut using a cooled cross-section polisher (CCP; IB19520CCP manufactured by JEOL Ltd.). [Diagram 5] 5(A) and (B) show a bead mill device used in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Preferred embodiments for carrying out the present invention will be described below with reference to the drawings. Definition
[0030] <m-CP particles> In the present invention, "<m-CP particles>" refers to tricalcium phosphate particles obtained by pulverizing β-phase tricalcium phosphate particles to a diameter of 0.1 to 0.5 μm by bead mill treatment and modifying them to an amorphous phase. m-CP particles can coordinate negative phosphate ions separated from metal or metalloid salts to positive ions separated from metal or metalloid salts due to the breakage of the crystal structure of calcium phosphate. The tricalcium phosphate contained in the biodegradable fiber of the embodiment of the present invention contains β-TCP particles and m-CP particles in a weight ratio of 5 to 50 to 95 to 50. However, if the amount of m-CP particles relative to β-TCP particles is less than 5:95, the high solubility effect of m-CP particles is less likely to occur. Conversely, if the amount of m-CP particles relative to β-TCP particles is greater than 50:50, the aggregation of m-CP particles becomes intense, and the amount of ion elution from m-CP particles may temporarily become too high, which may have an adverse effect on living tissues.
[0031] <Bead mill device> In the present invention, the term "bead mill device" refers to a grinding machine used to perform mechanochemical treatment on particles, which uses beads having a diameter of 0.015 to 3 mm as grinding media (FIG. 4). The diameter of balls, which are grinding media in a normal ball mill device, is 10 to 50 mm, whereas the diameter of beads used as grinding media in a bead mill device is 0.015 to 3 mm. By using small-diameter beads as grinding media, it is possible to give 100 to 500 times more energy to calcium phosphate particles than when balls having a diameter of 10 to 50 mm are used. In a planetary bead mill device, particles put into a vessel are alternately rotated and revolved, so that the beads used as grinding media apply stronger impact energy to the particles, resulting in grinding with higher grinding efficiency. There are different types and models of bead mill devices, but any of them can be used as the bead mill device of the present invention as long as it is possible to finely grind calcium phosphate particles with beads.
[0032] <Bead mill processing> In the present invention, "bead mill treatment" refers to a treatment in which beads are placed in the pot of a bead mill device, powder particles are added, and the device is rotated at high speed to impart a large amount of energy to the particles that make up the powder through intense mechanical impact. When calcium phosphate particles are subjected to a strong mechanical shock and a large amount of energy is applied to the particles by the bead milling process, the particles are pulverized to reduce their diameter, and the bonds that make up the particles are broken and ionized.
[0033] <Wet grinding> In the present invention, "wet milling" refers to a method in which beads are placed in a container and mixed with a slurry of powder and liquid, and the mixture is milled by stirring. This is contrasted with dry milling, which mills without mixing liquid (in air). When milling is performed dry in a bead mill, the milled particles are increasingly loaded together and become clogged, which makes it easy for hard aggregates to form during milling. Therefore, wet milling is used in the bead milling process of the present invention. In wet milling, H +If a polar liquid (e.g., water) is used, the crushed particles will form hydrogen bonds and aggregate. To avoid this, H + It is preferable to use a liquid that does not dissociate and has no polarity (e.g., acetone).
[0034] <Wet spinning method> "Wet spinning" generally refers to a method in which a polymer dissolved in a solvent is discharged from a nozzle into the liquid to form fibers. The wet spinning method used in the present invention is described in detail in WO2022 / 113888 (Method for producing a cotton-shaped bone regeneration material) and WO2023 / 228905 (Method for continuously producing a biodegradable fiber material containing inorganic filler particles using a wet spinning method, and a cotton-shaped bone regeneration material produced by the method).
[0035] EMBODIMENT 1 Fabrication of bone regenerative material consisting of biodegradable fibers containing β-TCP and m-CP particles 1. Preparation of m-CP particles ·Put β-TCP particles with a diameter of 0.5 to 5 μm into the zirconia pot (volume capacity 30 to 60 mL) of a planetary bead mill device together with 35 to 50 g of beads with a diameter of 0.5 to 1.4 mm in an amount that makes the apparent volume ratio of the two 1:2 to 4. Add 15 to 20 mL of acetone to this, and perform wet grinding by revolving and rotating the planetary bead mill device at a specified speed. Upon impact from the beads, the β-TCP particles are pulverized, the particle size decreases to 0.1-1.2 μm, the specific surface area increases 3-5 times, and the crystal structure of the β-TCP particles becomes partially amorphous, decreasing the degree of crystallinity to 50-10%.
[0036] 2.Spinning of biodegradable fibers containing β-TCP and m-CP particles 1) Preparation of spinning solution Mix β-TCP particles, m-CP particles, and PDLLGA in a weight ratio of 30-55:5-35:15-65, dissolve the polymer in acetone, mix overnight, and prepare a spinning solution with a polymer concentration of 17-23%. If the amount of PDLLGA resin is less than 15% by weight, it becomes difficult for the resin to bind the particles as a binder, making spinning difficult. Conversely, if the amount of PDLLGA resin is more than 65% by weight, the bioaffinity of calcium phosphate cannot be exhibited. 2) Wet spinning The particle dispersion prepared above is used as a spinning solution to spin biodegradable fibers by wet spinning. 3. Collection of cotton-like bone regenerative material After wet spinning, the entangled aggregate of spun biodegradable fibers is roughly removed of poor solvent (water, etc.) with a water-absorbing sheet, and dried overnight at room temperature to obtain cotton-shaped sample 1 (see FIG. 1).
[0037] 4. Properties of the obtained biodegradable fiber / bone regenerative material Biodegradable fibers with diameters of 60 to 200 μm are entangled to form a cotton-like structure. In the biodegradable fiber, the m-CP particles do not aggregate but are dispersed around the β-TCP particles (see Figures 2 and 3).
[0038] EMBODIMENT 2 Preparation of bone regenerative materials consisting of biodegradable fibers containing β-TCP particles and m-CP particles containing metal or metalloid ions 1. Preparation of m-CP particles containing metal or metalloid ions (1) β-TCP particle powder and metal (e.g. magnesium, silver) or semi-metal (e.g. silicon, boron) salt particle powder are mixed in a weight ratio of 0.99-0.90 to 0.01-0.1, and the powder mixture is placed in a zirconia vessel (volume capacity 30-60 mL) of a planetary bead mill together with 15-20 mL of acetone and 35-50 g of beads with a diameter of 0.6-1.4 mm, and the planetary bead mill is revolved and rotated at a specified speed. (2) Upon impact with the beads, the β-TCP particles are pulverized, decreasing their particle size and increasing their specific surface area, while the crystal structure of the β-TCP particles becomes partially amorphous, forming m-CP particles. Metal or metalloid salt particles fed into the zirconia vessel of the planetary bead mill are impacted by the beads, causing metal or metalloid ions to separate from the particles, and the separated positive ions coordinate with the phosphate ions (negative charge) of the m-CP particles. (3) After rotating the planetary bead mill at high speed for a certain period of time, the ions separated from the metal or metalloid salt particles are fixed in a coordinated state to the phosphate ions of the m-CP particles. The beads and the mixed powder are then separated by sieving and washed away, and the acetone is removed by placing the mixture in a 70°C oven overnight to recover the m-CP particles containing the metal or metalloid ions.
[0039] 2.Spinning of biodegradable fibers containing β-TCP particles and m-CP particles, recovery of cotton-like bone regeneration material, and properties of the obtained biodegradable fibers / bone regeneration material β-TCP particles, m-CP particles containing metal or semi-metal ions, and PDLLGA are mixed in a weight ratio of 30-55:5-35:15-65, dissolved in acetone to prepare a spinning solution, and biodegradable fibers are spun using a wet spinning method. The spun biodegradable fibers are dried to obtain cotton-shaped sample 2 (see Figure 1). The properties of the resulting biodegradable fiber / bone regenerating material are similar to those of Example 1, except that the m-CP particles contain metal or metalloid ions.
[0040] Experiment 1 <Contents of Experiment 1> Preparation of biodegradable fibers containing β-TCP particles, m-CP particles, and PDLLGA β-TCP particles (manufactured by Taihei Chemical Industry, diameter 0.5-5μm, average 1.2μm), m-CP particles (diameter 0.02-1.0μm, average 0.4μm), and PDLLGA were mixed in a weight ratio of 30:14:56, dissolved in acetone, and mixed overnight to prepare a spinning solution with a polymer concentration of 23.3%. Biodegradable fibers with fiber diameters of 100-120μm were spun by wet spinning using the spinning solution prepared above. The cross section of the spun biodegradable fibers was cut using a cooled cross-section polisher (CCP) (cooled to about -100℃ and ion milled by argon irradiation).
[0041] <Results of Experiment 1> SEM photographs of the cross sections of the biodegradable fibers spun in the above experiment are shown in Figures 3 and 4. In the SEM images of Figures 3 and 4, the bright areas are tricalcium phosphate particles (TCP) and the dark areas are PDLLGA resin. Because there is no chemical bond between the biodegradable fiber and TCP and their elastic moduli are significantly different, the grinding process puts a load on the large TCP particles, which tend to come off leaving the matrix polymer behind, resulting in a cross section full of holes. Judging from their size and shape, these holes are thought to be areas where TCP particles were originally embedded, with the polymer matrix remaining (the dark areas). Since the particle size of m-CP particles is small, on the submicron order, if they are completely embedded in the matrix, they will not come out. The white arrows in Figure 4 indicate m-CP particles that are near the surface of the holes. This photo shows the state in which m-CP particles are dispersed around β-TCP particles.
[0042] Experiment 2 <Contents of Experiment 2> Preparation of m-CP particles containing silver ions (1) β-TCP powder and Ag3PO4 powder (both manufactured by Taihei Chemical Industry Co., Ltd.) were mixed in a weight ratio of 99:1 to prepare 1.8 g of mixed powder. (2) 40.5g of beads with a diameter of 1 mm and 13.5g of acetone (=17ml) were placed in a zirconia vessel (volume capacity 45ml) of a planetary ball mill. With the beads / acetone in the vessel, it was immersed to about 80% of the vessel. 1.8g of the mixed powder prepared above was added thereto, and the ball mill was rotated at high speed with a revolution of 400rpm and a rotation of 800rpm. (3) When the planetary ball mill was rotated at high speed, the β-TCP particles were finely ground and the crystal structure of the β-TCP particles was partially amorphous due to the impact of the beads. Silver ions were separated from the Ag3PO4 particles by the impact of the beads, and the separated silver ions (positive charge) were coordinated to the phosphate ions (negative charge) of the amorphous β-TCP particles (m-CP particles). (4) The planetary ball mill was rotated at high speed for 2 hours and then allowed to stand, thereby fixing the Ag3PO4 particles in a coordinated state around the phosphate ions of the m-CP particles. (5) After the immobilization step, the zirconia beads were separated from the powder mixture by sieving and washing to recover the m-CP particles containing silver ions.
[0043] <Results of Experiment 2> (i) The beads used were 1 mm in diameter, and if they were 1 mm, they could be roughly recovered by passing them through a sieve with openings of about 125 μm and rinsing with acetone. If beads with a diameter smaller than 1 mm are used, the crushing effect increases, but it takes more time to recover them because a sieve with smaller openings must be used so that the beads do not fall through. (ii) The powder of particles prepared by wet bead milling of Ag3PO4 particles and β-TCP particles was immersed in a HEPES buffer solution, and the ion concentration of the solution was measured using ICP-AES. The silver ion concentration initially increased sharply and then gradually decreased. (iii) The m-CP particles containing silver ions prepared in Experiment 2 can be dispersed and incorporated into biodegradable fibers together with β-TCP particles, as in Experiment 1.
[0044] Experiment 3 <Contents of Experiment 3> Preparation of m-CP particles containing boron ions (1) β-TCP powder (manufactured by Taihei Chemical Industry Co., Ltd.) and B2O3 powder (special grade, manufactured by Kishida Chemical Co., Ltd.) were mixed in a weight ratio of 10-30:90-70 to prepare 1.8 g of mixed powder. (2) 40.5g of beads with a diameter of 1 mm and 13.5g of acetone (=17mL) were placed in a zirconia vessel (volume capacity 45mL) of a planetary ball mill. With the beads / acetone in the vessel, it was immersed to about 80% of the vessel. 1.8g of the mixed powder prepared above was added thereto, and the ball mill was rotated at high speed with a revolution of 400rpm and a rotation of 800rpm. (3) When the planetary ball mill was rotated at high speed, the crystalline structure of the β-TCP particles was partially amorphized by the impact of the beads. At the same time, the impact of the beads caused some of the bonds in the B2O3 particles to become distorted, broken, or formed new bonds, causing the particles to become amorphous. (4) The planetary ball mill was rotated at high speed for 2 hours and then allowed to stand, resulting in the amorphous B2O3 particles being fused to the amorphized β-TCP (m-CP). (5) After the immobilization step, the treated material was separated by sieving and washing with acetone to recover calcium phosphate particles containing boron ions.
[0045] <Results of Experiment 3> (i) The size of the particles obtained by grinding the coexisting β-TCP powder and B2O3 powder was approximately 0.1 μm to 1 μm, and the shapes were various. In addition, the number of aggregated particles increased as the amount of boron added increased. It is thought that the aggregation occurred when boron reacted with water in the air during the solid-liquid separation and drying process, and that the powder is highly reactive with moisture. (ii) The m-CP particles containing boron ions prepared in Experiment 3 can be dispersed and incorporated into biodegradable fibers together with β-TCP particles.
[0046] Although the present invention has been described above with reference to examples, the present invention is not limited to these examples, and is within the scope of the present invention as long as it has the structure or method described in the claims. Furthermore, the method for spinning the biodegradable fiber is not limited to the wet spinning method described in the examples, and other spinning methods such as electrospinning are also within the scope of the present invention as long as they can spin biodegradable fibers containing both β-TCP particles and m-CP particles. [Explanation of symbols]
[0047] 1. Biodegradable Fibers 10 β-TCP particles 20 m-CP particles
Claims
1. A bone regeneration material comprising a biodegradable fiber containing tricalcium phosphate particles, The bone regeneration material is formed of biodegradable fibers having an outer diameter of 60 to 200 μm that are entangled with each other to form a cotton-like shape, The biodegradable fiber contains 40 to 70% by weight of β-phase tricalcium phosphate particles (β-TCP particles) having a diameter of 0.5 to 5 μm, 5 to 15% by weight of tricalcium phosphate particles (m-CP particles) obtained by crushing the β-TCP particles to a diameter of 0.1 to 0.5 μm through a bead mill and modifying the particles into an amorphous phase, and the remainder being 55 to 15% by weight of PDLLGA resin, the biodegradable fiber is spun by a wet spinning method from a spinning solution prepared by dissolving the β-TCP particles, the m-CP particles, and the PDLLGA resin in acetone in a weight ratio of 40-70:5-15:55-15, stirring and mixing the resultant solution, so that the β-TCP particles are dispersed in the biodegradable fiber, and the m-CP particles are dispersed surrounding the β-TCP particles without agglomerating; After the bone regeneration material is implanted into an affected area, the m-CP particles dissolve in contact with a body fluid as the PDLLGA resin decomposes, releasing calcium ions and phosphate ions, and thereafter the β-TCP particles dissolve with a delay, gradually releasing calcium ions and phosphate ions continuously. A bone regeneration material comprising biodegradable fibers containing the tricalcium phosphate particles.
2. The bone regeneration material according to claim 1, wherein the m-CP particles are prepared by wet-grinding the β-TCP particles with acetone.
3. The bone regeneration material according to claim 1 or 2, wherein the m-CP particles carry metal or semi-metal ions.
4. The bone regeneration material according to claim 1 or 2, wherein the m-CP particles carry silver ions.
5. The bone regeneration material according to claim 1 or 2, wherein the biodegradable fibers are spun using a wet spinning method.
6. A method for producing a bone regenerating material comprising biodegradable fibers containing tricalcium phosphate particles, comprising: β-phase tricalcium phosphate particles (β-TCP particles) having a diameter of 0.5 to 5 μm are milled to a diameter of 0.1 to 0.5 μm by a bead mill to prepare amorphous phase modified tricalcium phosphate particles (m-CP particles); A spinning dope is prepared by mixing and stirring 40 to 70% by weight of the β-TCP particles, 5 to 15% by weight of the m-CP particles, and 55 to 15% by weight of the PDLLGA resin in acetone, as the remainder; By wet spinning using the spinning solution, a biodegradable fiber is spun in which the β-TCP particles are dispersed in the biodegradable fiber and the m-CP particles are dispersed surrounding the β-TCP particles without agglomeration; The spun biodegradable fibers are washed with ethanol and dried at room temperature to recover a cotton-like bone regeneration material. A method for producing a bone regenerating material comprising biodegradable fibers containing the tricalcium phosphate particles.
7. The method for producing a bone regenerating material according to claim 6, wherein the m-CP particles are prepared by wet-grinding the β-TCP particles with acetone.
8. The method for producing a bone regenerating material according to claim 6 or 7, further comprising a step of loading metal or metalloid ions onto the m-CP particles.
Citation Information
Patent Citations
Processing of biocompatible coating on polymeric implants
US20130066425A1
Production method for bone-regeneration material imparted with antimicrobial properties using inositol phosphate, and antimicrobial bone-regeneration material produced by said production method
WO2019221159A1
Mehtod for manufacturing flocculent material for bone regeneration
WO2022113888A1